Augmented Reality Bilingual Learning Pengenalan Barang dan Binatang untuk Anak TK - Rahayu, Sri; Tresnawati, Dewi; Gumelar, Agung (Institut Teknologi Garut, 2024)
In the current era of globalization and technological advances, mastery of English is very important, but conventional teaching processes are still widely applied. There is a need to develop more interactive and effective learning media, especially for kindergarten children, which combines English and Indonesian. The aim of this research is to develop an Augmented Reality (AR) based application that can introduce the names of items and animals in two languages ”‹”‹(Indonesian and English) to kindergarten children. This application is designed to provide a fun and interactive learning alternative outside of school hours. Methodology: This research uses the Multimedia Development Life Cycle (MDLC) methodology, which includes the stages of Literature Study, Concept, Design, Material Collection, Assembly, Testing, and Distribution. This application was developed using the Android platform with the application of Augmented Reality technology to display interactive 3D objects. Results: The application developed successfully met the needs of language learning and interactivity. Test results show that 89% of 37 users (kindergarten teachers and parents) involved in beta testing gave positive feedback to this application, confirming its effectiveness in supporting learning activities. This application offers a new learning method that can replace or complement conventional learning methods in a more interesting and interactive way. This not only supports dual language learning from an early age but also integrates the latest technology in education.